2014
DOI: 10.3109/13880209.2014.889720
|View full text |Cite
|
Sign up to set email alerts
|

Salvia miltiorrhizacompounds protect the liver from acute injury by regulation of p38 and NFκB signaling in Kupffer cells

Abstract: Context: Salvia miltiorrhiza Bunge is a traditional Asian medicine used to treat cerebral and cardiac ischemia. However, the effects of the active compounds of S. miltiorrhiza on liver damage are unclear. Objective: In this study, we tested the effects on acute liver injury of crude S. miltiorrhiza extracts from roots as well as neotanshinone B, dehydromiltirone, tanshinol A, tanshinone I, dihydrotanshinono I, neotanshinone A, cryptanshinono, tanshinone II A, and salvianolie acid B from purified S. miltiorrhiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The case of Radix Salvia miltiorrhiza was used for demonstrating the potential application of this method. Substantial evidence has shown that Tanshinone IIA is one of the main pharmacologically active ingredients in Radix Salvia miltiorrhiza . Our radar chart analysis suggests that Tanshinone IIA is a typical strong retention compound in the C 18 column (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 69%
“…The case of Radix Salvia miltiorrhiza was used for demonstrating the potential application of this method. Substantial evidence has shown that Tanshinone IIA is one of the main pharmacologically active ingredients in Radix Salvia miltiorrhiza . Our radar chart analysis suggests that Tanshinone IIA is a typical strong retention compound in the C 18 column (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Active ingredients of Salvia miltiorrhiza Bunge can also exert hepatoprotective effect from CCl 4 -induced liver injury in rats. The protective effect may be due to inhibition of NF-kB and p38 signaling in liver Kupffer cells [ 52 ]. Treatment of chronic iron-overloaded mice with Salvia miltiorrhiza Bunge will improve the hepatic morphology, decreasing iron deposition as well as inhibiting the expression of type I and type III collagen, TGF-beta mRNA, and increase the expression of matrix metalloprotein-9 (MMP-9) mRNA in the liver.…”
Section: Recent Research On the Roles Of Herbs And Phytochemicals mentioning
confidence: 99%
“…Sm compounds protect the liver from acute injury by the regulation of p38 and NF-kB signaling in Kupffer cells (Yue et al, 2014). S. plebeia suppresses atopic dermatitis-like skin lesions .…”
Section: Anti-inflammatory and Antioxidant Effectsmentioning
confidence: 99%